Pemanfaatan air hujan sebagai sumber air utama kampus Universitas Papua Manokwari - Mariones Ruamba; Ishak Semuel Erari; Rosalina Mirino; Abdul Muis Muslimin (Jurnal Natural, 2024)
The purpose of this study was to determine the amount of water storage obtained from rainwater collected through the roof of the building and the monthly water needs at the University of Papua (Unipa) Manokwari Campus. The results showed that the input of rainwater per year was 3.54 times more than the water usage on campus. All buildings on the Unipa Manokwari campus had a water surplus per month, except for the Faculty of Economics and Business building which had a water deficit from October to December. Buildings with a water surplus can act as buffers for buildings with a water deficit.